REVIEW ON EVALUATING THE ROLE OF NSAIDS FOR THE TREATMENT OF ALZHEIMER’S DISEASE - P. R., KRISHNENDU; B., ARJUN; K., VIBINA; T. S., NIVEA CLEO; N. K., DRISYA; MOHANDAS, RADHIKA; ZACHARIAH, SUBIN MARY; ZACHARIAH, SUBIN MARY (International Journal of Applied Pharmaceutics, 2021)
Recently, several studies have been reported that nonsteroidal anti-inflammatory drugs can fight against neurodegenerative disorders by various mechanisms. Currently, available therapies of neurodegenerative disorders (NDs) provide only symptomatic relief. This is the point at which we need an alternative that acts on the root cause of disease. Parkinson’s disease and Alzheimer’s disease are the two NDs concentrated here. Since the drug profile is already known, drug repurposing is a promising technique in research, thereby reducing the cost and period effectively. Epidemiological studies on various nonsteroidal anti-inflammatory drugs (NSAIDs) showed good results, but when it came to clinical studies the results are found to be poor. Hence, it can be concluded that NSAIDs provide its neuroprotective activity on its long-term use only, as the brain accessibility of this kind of drug is poor due to its lower lipophilicity.